THE THEORETICAL FRAMEWORK OF LOGISTICS IN ENTERPRISES (Development Service Industry Management, 2023)
The majority of historical works focus on logistics to ensure military activities in different years and eras.  For the ancient Greeks, logistics was considered the 'logistic art' or 'the art of reasoning and computing'. Logistics has been developed in different areas, such as industry, military operations, transportation, and information technology. The article discusses the essence of logistics and logistic activity and offers author’s definitions. As we believe, logistics should be understood as a comprehensive system of planning, coordination, and control that pertains to managing material resource flows, goods, services and information from supply to the end consumer. The primary objective of logistics is to ensure the optimal and efficient operation of the supply chain  to meet the needs of consumers and maximize the profitability of business processes. The concept of logistics activity should be viewed as a set of solutions, activities, and processes that aim to organize and optimize material, information, and financial flows to accomplish the company's objectives and satisfy consumer demands. Logistics support is the key to logistics activities, and includes the entire range of operations and activities that ensure the functioning of the logistics system of the company: Supply/purchase, inventory management, production, warehousing, transportation, and sales are just some of the things covered. Logistics support allows enterprise management to form the necessary logistics flows. They allow you to flexibly respond to market requests and implement operational processes at the appropriate level. This significantly improves the quality of operational management. Logistics support is achieved by effectively managing material and information flows and optimizing them to minimize costs, ensure quality, and meet deadlines.
Keywords: logistics; logistic activity; logistic management; logistic support; logistic support system